Pengendalian Internal Sistem Penggajian: Esensi Langkah Ekspansi UMKM (Studi pada Usaha Dagang di Kabupaten Ngawi Jawa Timur) - Ria Zulkha Ermayda; Dhika Maha Putri; Dwi Narullia (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
One of the effects of Pandemic Covid-19 is the drop in demand which resulted in disruption of the supply chain. More than 50% of Micro, Small and Medium Enterprises (MSMEs) in Indonesia potentially collapsed into bankruptcy as a result of the pandemic. On the other hand, the existence of MSMEs has a major contribution to the Indonesian economy. This is the main reason for the importance of maintaining the business continuity of the MSME sector, one of which is by implementing an efficient and effective accounting information system and internal control. Internal control of the payroll system is an important aspect because MSMEs are still very dependent on human resources (HR) in carrying out their business processes. This research is a qualitative case study which aims to examine the information system and internal control implemented by UD X. The data were obtained through interviews and documentation to be analyzed. Triangulation of methods and sources was carried out as a validation step for this research. The results of the study conclude that in general, internal control in the UD.X payroll system has met the aspects and objectives of internal control. However, to control employee attendance, an evaluation is needed. Improving the quality and motivation of employees is needed so that the willingness, discipline and productivity of employees will increase. One of the controls that can be applied by UD.X is through the provision of rewards to employees with good performance, balanced with continuous evaluation of the frequency of employee attendance.